Qur’anic Reading Habits and Learning Concentration: A Strategic Approach in Islamic Education Curriculum at Elementary Madrasahs - Mursal, Aziz; Siregar, Tarmiji; Nasution, Nur Susila (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2026)
Low levels of students’ learning concentration at the elementary madrasah level highlight the need for strategic approaches within Islamic education that integrate cognitive and spiritual dimensions. Previous studies have predominantly examined Qur’anic reading practices as instruments for character development and religious literacy, while limited attention has been given to their contribution to students’ learning concentration in formal educational settings. The purpose is to examine Qur’anic reading habits as a strategic approach to enhancing learning concentration within the Islamic education curriculum at elementary madrasahs. A qualitative case study design was employed, with data collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, complemented by thematic analysis. The findings indicate that habituation of reading the Qur’an, particularly Juz ‘Amma, conducted daily for 15 minutes before classroom instruction using the tartil method, significantly improves students’ learning concentration. The practice also contributes to the development of religious character traits, including discipline, responsibility, and respect for the Qur’an. Implementation supported by collaboration between teachers and parents, alongside ability-based student grouping, effectively addresses challenges related to differences in recitation skills and understanding of tajwid. The originality lies in positioning Qur’anic reading habits as an integrated pedagogical strategy that simultaneously strengthens cognitive concentration and spiritual character formation, offering a holistic framework for Islamic education curriculum development at elementary madrasahs.